A paper-making transformation: from cellulose-based superwetting paper to biomimetic multifunctional inorganic paper. Issue 39 (21st September 2020) - Wen, Gang; Guo, Zhiguang
Abstract : In this review, we have summarized the recent research progress on cellulose-based paper and inorganic paper, and emphasize the multi-functional applications of inorganic paper. Abstract : Even in the age of electronic information, paper has always played an important role in most fields. Conventional cellulose-based paper is highly porous, rough, hydrophilic and possesses a single function. In this review, the development and challenges of cellulose-based paper are illustrated. In this case, inorganic paper can be regarded as the candidate material for the paper-making field. This review aims to summarize the most recent progress on inorganic paper. Significantly, different kinds of inorganic raw materials for designing inorganic paper will be presented, followed by a summary of their emerging applications. The raw materials can be divided into four parts: hydroxyapatite-based, silicon-based, carbon-based, as well as metal–organic framework-based materials. The inorganic paper produced by these raw materials has many applications, such as fire-resistance, pollutant treatment, actuator, flexible electronics and energy storage. The development of inorganic paper may provide new inspiration for the paper-making field.